Problems That Principals Face In School Administration - Engin Aslanargun (Gaziantep University Journal of Social Sciences, 2012)
Transformation is the key concept in this century that should be taken into consideration in organization anyway. Educational organizations are also under the influence of such transformation as in the case for others, the role of administrators have taken more significance that leads them to apply emerging approaches in organizational life. The purpose of this study is to define the communicative problems that principals experience in school settings and possible problem solving behaviors towards teachers. 7 principals administering schools in the town of Akçakoca, in Düzce, included the study with qualitative case design and purposive, maximum sampling procedure. It was appeared that principals have displayed in some cases similar and different administrative behaviors while tackling with communicative and problem solving conditions. It was revealed that principals tend to do their jobs within limited scope and structure based administrative style instead of consideration as a result of this study. School climate that is essential for effective learning and teaching process have been asserted to be ignored or taken less significance behind the structural and material matters